2023
DOI: 10.3389/fonc.2023.1239375
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a novel prognostic model for intrahepatic cholangiocarcinoma based on a combined scoring system of systemic immune-inflammation index and albumin-bilirubin: a multicenter study

Haofeng Zhang,
Qingshan Li,
Guan Huang
et al.

Abstract: BackgroundThe degree of inflammation and immune status is widely recognized to be associated with intrahepatic cholangiocarcinoma (ICC) and is closely linked to poor postoperative survival. The purpose of this study was to evaluate whether the systemic immune-inflammatory index (SII) and the albumin bilirubin (ALBI) grade together exhibit better predictive strength compared to SII and ALBI separately in patients with ICC undergoing curative surgical resection.MethodsA retrospective analysis was performed on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In our study, bilirubin levels within a week before receiving immunotherapy were related to the total survival time of the patients (mOS: 1508 vs. 263 days), with higher levels indicating a worse prognosis. Bilirubin levels affect patients with cholangiocarcinoma's prognosis in several ways: Patients with hilar cholangiocarcinoma with higher bilirubin levels at diagnosis may not benefit from surgery (34); The albumin bilirubin (ALBI) grade, which combines bilirubin and albumin levels, is an independent prognostic factor for OS and PFS in intrahepatic cholangiocarcinoma (35,36). The analysis of FIB-4, SII, NLR, PLR, and PNI showed that FIB-4 is an independent risk factor for OS in patients with cholangiocarcinoma undergoing immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, bilirubin levels within a week before receiving immunotherapy were related to the total survival time of the patients (mOS: 1508 vs. 263 days), with higher levels indicating a worse prognosis. Bilirubin levels affect patients with cholangiocarcinoma's prognosis in several ways: Patients with hilar cholangiocarcinoma with higher bilirubin levels at diagnosis may not benefit from surgery (34); The albumin bilirubin (ALBI) grade, which combines bilirubin and albumin levels, is an independent prognostic factor for OS and PFS in intrahepatic cholangiocarcinoma (35,36). The analysis of FIB-4, SII, NLR, PLR, and PNI showed that FIB-4 is an independent risk factor for OS in patients with cholangiocarcinoma undergoing immunotherapy.…”
Section: Discussionmentioning
confidence: 99%